A case study on lentil to demonstrate the value of using historic data stored in genebanks to guide the selection of resources for research and development projects - Nadiia Vus; Olha Bezuhla; Hervé Houtin; Florence Naudé; Antonina Vasylenko; Anthony Klein; Oleh Leonov; Nadim Tayeh (Genetic Resources, 2024)
Plant genetic resources are essential for sustainable agriculture and a secure and stable global food supply. One of the most important pulses and an integral part of a healthy diet is lentil (Lens culinaris Medik.). The National Centre for Plant Genetic Resources of Ukraine (NCPGRU), based in Kharkiv, manages a lentil collection of 1,140 accessions. In 2019, the first exchange of 37 lentil accessions between NCPGRU and a French research team took place. This exchange was accompanied by the transfer of phenotyping data for multiple traits. Considering that data collected in different environments provide important information on trait stability, the lentil accessions were phenotyped under new conditions through field research. This research allowed a comparative analysis of agroclimatic conditions for lentil cultivation in Ukraine (Kharkiv region) and France (Bourgogne-Franche-Comté region). The possibility of using genebank information to guide plant material selection for research and development projects was assessed. As a result, six lentil genotypes that performed well in different environments were selected. This allowed the identification of genotypes with the highest yield potential: UD0600086, UD0600145, UD0600437, UD0600530, UD0600550 and UD0600638. Genotypes recommended for use in breeding to produce high-yielding, relatively stable lentil varieties were successfully selected in the application case of this study, confirming that the information in the trait database of the NCPGRU Genebank is an important resource for predicting the characteristics of lentil accessions. Of the eight accessions selected by GGE biplot analysis using field research, five were predicted to be more promising by previous genebank data.